Change Management: A Bibliometric Mapping of Research Fronts and Collaboration Networks - Loso Judijanto; Wahyudin Wahyudin (West Science Business and Management, 2026)
This study aims to map the intellectual structure, research fronts, and collaboration networks in the field of change management using a bibliometric approach. Data were collected from the Scopus database, covering publications related to change management within a specified time frame, and analyzed using VOSviewer to generate co-occurrence, density, and network visualizations. The results reveal that change management research has evolved into a highly interdisciplinary domain, with dominant themes centered on human-related factors and environmental issues, particularly climate change and sustainability. The findings indicate a significant shift from traditional organizational change models toward broader systemic perspectives that integrate public health, ecological transformation, and social adaptation. In addition, emerging topics such as machine learning and risk assessment highlight the growing role of data-driven approaches in understanding and managing complex change processes. The collaboration network analysis suggests that while the field demonstrates increasing connectivity, it remains partially fragmented across disciplinary boundaries. This study contributes by providing a comprehensive overview of the development and structure of change management research, identifying key themes and emerging trends, and offering directions for future research to enhance integration and innovation in the field.